2014
DOI: 10.1111/php.12234
|View full text |Cite
|
Sign up to set email alerts
|

Practical Labeling Methodology for Choline‐Derived Lipids and Applications in Live Cell Fluorescence Imaging

Abstract: Lipids of the plasma membrane participate in a variety of biological processes, and methods to probe their function and cellular location are essential to understanding biochemical mechanisms. Previous reports have established that phosphocholine-containing lipids can be labeled by alkyne groups through metabolic incorporation. Herein, we have tested alkyne, azide and ketone-containing derivatives of choline as metabolic labels of choline-containing lipids in cells. We also show that 17-octadecynoic acid can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
(99 reference statements)
0
16
0
Order By: Relevance
“…Cho-phospholipids can be tracked via fluorescence microscopy using choline analogs such as propargyl-choline [ 11 ] and azido-choline ( AzCho, Fig. 4a ) [ 31 ]. Azide-functionalized analogs such as AzCho are especially versatile metabolic labeling substrates, since in addition to modification by CuAAC, they are also susceptible to strain-promoted ligation with cyclooctynes—a reaction referred to as “copper free click chemistry” that is compatible with live cells [ 16 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cho-phospholipids can be tracked via fluorescence microscopy using choline analogs such as propargyl-choline [ 11 ] and azido-choline ( AzCho, Fig. 4a ) [ 31 ]. Azide-functionalized analogs such as AzCho are especially versatile metabolic labeling substrates, since in addition to modification by CuAAC, they are also susceptible to strain-promoted ligation with cyclooctynes—a reaction referred to as “copper free click chemistry” that is compatible with live cells [ 16 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple reports have showcased the efficacy of labeling strategies for elucidating these complex processes. Cairo and co-workers followed up on lipid metabolic labeling using PCho, AECho and a ketone-containing choline (Li et al, 2014). In doing so, they explored various live cell imaging protocols and showed that lipid dynamics could be studied via fluorescence recovery by photobleaching, and that cells could be attached onto functionalized surfaces by click chemistry.…”
Section: Investigations Of Lipid Metabolism Trafficking Localization and Protein Bindingmentioning
confidence: 99%
“…Two analogs of Cho, PCho and 1-azidoethyl-choline (AECho) ( Fig. 1B), have been used to metabolically label PC in mammalian cells (27,39,40). Both analogs react with an azide or alkyne after incorporation into PC to allow further detection.…”
Section: Downloaded Frommentioning
confidence: 99%
“…M9 minimal medium with maltose (M9+malt, per liter containing 0.3% KH2PO4, 0.6% Na2HPO4, 0.5% NaCl, 0.1% NH4Cl, 2 mM MgSO4, 0.1 mM CaCl2, 0.2% maltose, sterile filtered) was used for washing or flow cytometry medium. Choline chloride (Cho) was purchased from Sigma Aldrich and propargylcholine bromide (PCho) from Aobious; 1-azidoethyl-choline iodide (AECho) was synthesized as described (40). AlexaFluor488 DIBO alkyne (Alexa488-DIBO) and AlexaFluor488 sDIBO alkyne (Alexa488-sDIBO) were obtained from Thermo Fisher Scientific.…”
Section: Bacterial Strains Growth Conditions and Materialsmentioning
confidence: 99%